Exploring modes of entry into international markets: direct investment or contractual relations - Fernandes, Rui; Gouveia, Borges; Pinho, Carlos (Journal of Business Economics and Management, 2014)
We consider the multinational company's decision on whether to enter a new foreign market using direct investment by establishing a subsidiary, direct exporting or contracting a local distributor, with the option to invest later. We develop two models, based on the real options theory, to support such decisions. The option on direct exporting or on a local distributor allows the firm to minimize risks by finding out if the market is large enough to support future direct investment. We find the direct investment to be the desirable mode of entry in large markets subject to low demand uncertainty. Overall, the investigation increases the knowledge related with exploring new markets subject to demand uncertainty, valuing the flexibility of present and future options.